2003
DOI: 10.1046/j.1440-1703.2003.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and rarity hotspots and conservation of butterfly communities in and around the Aokigahara woodland of Mount Fuji, central Japan

Abstract: In central Japan, Aokigahara woodland is considered to be one of the most natural areas around Mount Fuji and a core area in the conservation of the biodiversity of Mount Fuji. We chose butterflies as an indicator species of biodiversity and examined six communities in and around the woodland in 2000 using transect counts to examine and search for diversity and rarity hotspots and their associated landscapes. The results showed that butterfly species richness and species diversities H′ 1/λ were significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on butterflies and moths have demonstrated the relationship between lepidopteran species richness and plant species richness (26,27). However, the local movements of adult butterflies might be influenced by nectar resources.…”
Section: Discussionmentioning
confidence: 99%
“…The other reason is that these two sections include forest edge. It is well known that species richness of butterflies is highest at the forest edge (Hill et al 1992;Ishii et al 1995;Ishii 1996;Kitahara and Watanabe 2003). However, since forest edge is a border between two different vegetation types, forest edge contains diverse vegetations as such.…”
Section: Discussionmentioning
confidence: 99%
“…Several butterfly studies in Japan have stressed on the importance of forest edge for conservation because of high butterfly diversity (Ishii 1996) and presence of endangered species (Kitahara and Watanabe 2003). In the case of Kitahara and Watanabe (2003), these endangered species depend on semi-natural grasslands along the forest edge. However, regrettably, semi-natural grasslands have been already lost from most satoyama areas in Japan (Tabata 1997;Inoue 2005).…”
Section: Discussionmentioning
confidence: 99%